YOUNG LEARNERS' PROCESSING OF MULTIMODAL INPUT AND ITS IMPACT ON READING COMPREHENSION: AN EYE-TRACKING STUDY. Issue 3 (15th July 2020) - Pellicer-Sánchez, Ana; Tragant, Elsa; Conklin, Kathy; Rodgers, Michael; Serrano, Raquel; Llanes, Ángels
Abstract: Theories of multimedia learning suggest that learners can form better referential connections when verbal and visual materials are presented simultaneously. Furthermore, the addition of auditory input in reading-while-listening conditions benefits performance on a variety of linguistic tasks. However, little research has been conducted on the processing of multimedia input (written text and images) with and without accompanying audio. Eye movements were recorded during young L2 learners' ( N = 30) processing of a multimedia story text in reading-only and reading-while-listening conditions to investigate looking patterns and their relationship with comprehension using a multiple-choice comprehension test. Analysis of the eye-movement data showed that the presence of audio in reading-while-listening conditions allowed learners to look at the image more often. Processing time on text was related to lower levels of comprehension, whereas processing time on images was positively related to comprehension.